Influence of layer thickness of 3D printed polyamide against temperature - Nabilah Afiqah Mohd Radzuan,; Nuraina Balqis Zainal,; Farhana Mohd Foudzi,; Abu Bakar Sulong,; Zaliha Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Polyamide is one of the materials in 3D printing that can produce valuable products to meet the needs of the industry. Previous studies have proven that the layer thickness of the 3D printed material and the increase in temperature affect the mechanical and physical properties. However, only a few studies involve polyamide material as a test material, especially in analyzing the influence of the layer thickness of the printed material and the increase in temperature on the mechanical and physical properties of polyamide. Therefore, the bending properties of polyamide with different layer thicknesses at 0.1 mm, 0.2 mm and 0.3 mm and the tensile properties of the material at different temperatures at room temperature, 75˚C and 110˚C will be studied. This study will involve polyamide (PA) materials printed at three different layer heights using the Fused Deposition Modelling (FDM) process. Bending and tensile tests at different temperatures from 27˚C to 110˚C are conducted using the Instron Universal Testing Machine. The study results show that the layer height of 0.3 mm exhibits the highest flexural strength at an average rate of 11.05 MPa compared to 0.1 mm (6.7 MPa) and 0.2 mm (9.6 MPa). The tensile strength decreases when the temperature elevates, making the temperature of 110˚C have the lowest tensile value (1.591 MPa) compared to the temperature of 75˚C (1.6MPa) and 27˚C (2.1MPa). Several material characterizations such as SEM, TGA, DMA, DSC and density have been performed to study the microstructure and influence of tensile test temperature on the mechanical properties of polyamide